Understanding Preferences for Addressing Spirituality Among Adults Seeking Outpatient Mental Health Care. Issue 6 (June 2020) - Currier, Joseph M.; Stevens, Laura T.; Isaak, Steven L.; Smith, Tracey; Zlomke, Kimberly
Abstract : Abstract: Focusing on 472 religiously heterogenous adult patients seeking psychotherapy at a university-based outpatient clinic, this brief report examined (1) these patients' preferences about clinicians appreciating their religion and/or spirituality (R/S) backgrounds (spiritually affirming) and addressing spiritual concerns in treatment (spiritually integrated) and (2) role of demographic factors and psychological functioning in predicting preferences for R/S integration. Analyses revealed that more than half of patients reported moderate or greater importance for spiritually affirming care and one-third hoped to address spiritual issues. Furthermore, these factors emerged as indicators of stronger preferences for R/S integration: female sex, racial minority status (African American, Native American), history of marriage (past and present), affiliation to organized religion (Christianity, Islam), and importance placed on R/S. In general, findings suggest that most patients seeking psychotherapy in a university-based clinic in southern Alabama might desire a spiritually affirming approach, and a smaller subset prefer an approach in which R/S is integrated into treatment.